A retrospective review of renal injuries and clinical outcomes correlated to AAST grading system at Siriraj Hospital - L. Somcharit (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF Thailand| 2020 Objective: To compare the AAST renal injury grading system of 1989 with the revision of 2011, in the aspect of surgeons’ decisions and patient management at Siriraj Hospital. This study also aims to create confidence among radiologists to select the most accurate grading system to analyze renal injuries. Materials and Methods: A retrospective study of 35 renal trauma patients who visited the Division of Trauma Surgery at Siriraj Hospital from January 2011 to December 2016. Contrast-enhanced MDCT of abdomen were performed and were classified according to the American Association for Surgery of Trauma grading system (AAST). The demographic data, clinical data, trauma score and management considerations also collected for each patient. Results: Twenty-one of 35 patients were managed by non-operative management (NOM). The others were managed by operative procedures including interventional radiology. Grade IV was the most common injury in these two groups. In NOM group, mean Injury Severity Score (ISS), Revised Trauma Score (RTS), survival probability (Ps) by Trauma Injury Severity Score (TRISS) were 18, 7.73 and 97.99%, respectively. In operative and interventional radiology management group, mean ISS, RTS, and Ps of TRISS were 23, 7.64 and 95.03%, respectively. There is no significant statistical difference in hospital stay, number of surgical and interventional radiology management of these two grading systems. Conclusion: The AAST grading systems of 1989 and 2011 are not statistically different from the perspective of management and clinical outcome. However, radiologists need to inform surgeons of MDCT findings, such as extra-luminal contrast extravasation or vascular lesion, which are not addressed in the 1989 or in the 2011 grading systems, for proper management.